A NEW ROLE OF CAUSATION THEORY TOWARDS ACHIEVING ECONOMIC CONTRACTUAL EQUILIBRIUM: MONITORING THE ECONOMIC EQUILIBRIUM OF THE CONTRACT - Amayreh, Osama Ismail; Zakri, Izura Masdina Mohamed; Tehrani, Pardis Moslemzadeh; Shandi, Yousef Mohammad (Indonesia Law Review, 2019)
The phrase “who says contractual, says justice” “qui dit contractuel dit juste” does not fully express the truth of our present reality, where the phrase itself falls into doubt, since the contract does not always result in fair obligations, as the contract is an expression of often unequal wills. In this regard, the French judiciary realized that the absence of justice in the contract might arise as a result of the contractual freedom afforded to the contracting parties and, thus, they developed the idea of Commutative Justice in the contract, such as the Piller’s decision, which is considered one of its most important applications. However, the causation theory in the Palestinian Civil Code Draft and the Indonesian Civil Code was limited to monitoring the matter of the existence of the corresponding obligation whatever it was. In this context, this paper seeks to prove that the provisions of the causation theory in the Palestinian Civil Code Draft and the Indonesian Civil Code can be used as a means of monitoring the economic contractual equilibrium of the contract. To do so, the legal provisions of the causation theory should be analysed in a comparative analytical approach with the French judicial decisions to illustrate the Palestinian and Indonesian legislative deficiencies and the need for adopting the French judicial approach.